COUNTERINSURGENCY IN NIGERIA: A REVIEW OF THE COUNTERINSURGENCY APPROACHES OF NIGERIA AGAINST THE ISLAMIST BOKO HARAM - Modu Lawan Gana; Hadiza Mali Bukar (ADISAM Publisher, 2022)
This is a review work. The narrative study analyses the various counterinsurgency options adopted by the Nigeria government in combating the Islamist Boko Haram in the country’s north. The Boko Haram is a radical Islamic fundamentalist that is opposed to all forms of western civilization including formal school, democracy, rule of law, party politics and secularism. It therefore erupts to violence to forcedly establish an Islamic State to be adjudicate by Islamic Injunctions of Qur’an and Hadith. The mindless violence since 2009 have left thousands of people death with properties worth millions of dollars destroyed. This article revealed that as options of combating the insurgency, the government have resorted to multifaceted strategies involving people-centered, enemy-centered and civilian base counterinsurgency operation. The dominant approach however remained the enemy-centered campaign; a strategy that involve the excessive deployment of troops and hot pursuit toward the perpetrators of the violence. The article recommends that as panacea to terminate the insurgent hostilities, government should focus on the root causes of the insurgency. Others are abolishment of key drivers inducing recruitment to the insurgent camps.